Capital, state and labour in the enigma of Baltic 'post-Communist' transformation - Salyga, Jokubas (2020)
This thesis unearths the social conditions and processes undergirding the enigma of ‘post-communist’ transformation in Estonia, Latvia and Lithuania. It transgresses the limitations beleaguering orthodox political economy, area studies and neoclassical sociology literatures by reconstructing a historical materialist framework. The framework aids the study of social change through the prisms of continuity in the forms of class-constituted rule, geographical and societal unevenness as well as intra- and inter- class conflict.